Screening Polimer Untuk Eor (Enhanced Oil Recovery) Di Lapangan “X” Minyak Cekungan Sumatera Tengah - Septiana, Dwi; Helwani, Zuchra; Abdurrahman, Muslim (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2022)
Oil is the energy source that people demand and use the most right now. Recent years have seen a lot of interest in polymer flooding as a cutting-edge chemical-based enhanced oil recovery (EOR) solution. Field X Minyak Cekungan Sumatera is acceptable for chemical EOR (Polymer) testing with a success range of up to 70%. The polymer solution will follow the channel that the water has created, and because of its high viscosity, it tends to "block" this area of the reservoir, allowing previously immobilized oil to start flowing. This can improve sweep efficiency. In this study, four polymers will undertake screening tests on the basis of compatibility, concentration, viscosity vs. shear rate, filtration, screen factor, and thermal stability. The best results is polymer 2 after polymer screening included passing the compatibility test, producing the best viscosity compared to the other three polymers at the same concentration, FR 1.2, having the best screen factor value compared to the other three polymers, and passing the thermal stability test.